2013
DOI: 10.1063/1.4798822
|View full text |Cite
|
Sign up to set email alerts
|

Structural, magnetic, and magnetoelastic properties of magnesium substituted cobalt ferrite

Abstract: The effects of substituting Mg on the structural, magnetic, and magnetostrictive properties ofcobalt ferrite have been investigated. Comparable values of lattice parameter were obtained for the Mg-substituted samples. Saturation magnetization continuously decreased with increase inMg concentration. Peak-to-peak magnetostriction amplitude and strain sensitivity had a similar dependence on Mg concentration. Keywords

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 7 publications
3
20
2
Order By: Relevance
“…9. The strain derivative obtained at x ¼ 0 is lower than that reported for un-substituted cobalt ferrite in previous studies 13,14,24 but comparable to that reported in another study. 7 This may be related to the processing conditions.…”
Section: Magnetostrictive Propertiescontrasting
confidence: 52%
See 1 more Smart Citation
“…9. The strain derivative obtained at x ¼ 0 is lower than that reported for un-substituted cobalt ferrite in previous studies 13,14,24 but comparable to that reported in another study. 7 This may be related to the processing conditions.…”
Section: Magnetostrictive Propertiescontrasting
confidence: 52%
“…Strain derivative is often enhanced at low cation concentration but decreases at higher concentrations. 3,7,13,14 Some exceptions are Ga-substitution 12 for which strain derivative was enhanced at relatively higher Ga concentration (x ¼ 0.4 at 300 K) and Mg-substitution 24 for which strain derivative decreased with Mg substitution. In those studies, Ga and Mg were substituted for Fe.…”
Section: Magnetostrictive Propertiesmentioning
confidence: 99%
“…and Mg 2? [19,23] in cobalt ferrite reduces the net magnetization of B-site at a greater extent than at the A-site. Therefore, overall magnetization decreases as the substituent concentration increases in the spinel lattice.…”
Section: Magnetic Characterizationmentioning
confidence: 95%
“…The coercivity increase from 36 to 112 when the crystallite size decreases from 38 to 27 nm. The decrease in coercivity is due to the expected crossover from a single domain to multidomain as particle size increases from 27 to 38nm [33]. The existence of the superparamagnetic behaviour of the synthesised particle is attributed to the finite crystallite size and the shape of the material [34].…”
Section: E Vsm Analysismentioning
confidence: 99%